A Midsummer Night's Dream - Shakespeare, William; Edited by Holland, Peter (New York Oxford University Press, 1998)
A Midsummer Night's Dream" is perhaps the best loved of Shakepeare's plays. It brings together aristocrats, workers, and fairies in a wood outside Athens, and from there the enchantment begins. The introduction to this edition pays particular attention to dreams and dreamers.
Include Appendix and Index
Autre tirage : 2001.
Keywords: Greece--Athens -- Courtship -- Theseus, King of Athens